Sulfur Isotopic Analysis and Sulfur Source Study of Phosphorite-associated Sulfate from the Ediacaran Doushantuo Formation in Guizhou Province - LI Xuanbo; WANG Ruimin; HUANG Tianzheng; SHUAI Gewei; SHEN Bing (Yankuang ceshi, 2022)
BACKGROUND Phosphate deposit of the Ediacaran Doushantuo Formation in Guizhou province is a typical representative of the global phosphorite formation event in the late Neoproterozoic, which is closely related to climate change and evolution of life. However, the current research on the deposition of phosphorus deposits is limited to the mechanism of phosphorus formation and the source of phosphorus, and research on the phosphorus formation process of this deposit and its correlation with the paleo-ocean environment of the same period by isotopic geochemical indicators is relatively weak. OBJECTIVES In order to determine the sulfur source of phosphorite-associated sulfate. METHODS Based on the field section observation and the study of petrological characteristics under the microscope, elemental analyzer-isotope ratio mass spectrometry (EA-IRMS) was used to measure the sulfur isotopic composition of phosphorite-associated sulfate from the Ediacaran Doushantuo Formation. RESULTS: The sulfur isotopic composition of phosphorite-associated sulfate ranged from 32.7‰ to 36.9‰ (n=32, mean=34.1‰), which was 11‰ lower than that of the seawater of the same period, indicating that the phosphorite-associated sulfate was not all from the surface seawater. CONCLUSIONS The idealized early ocean (>520Ma) chemical zoning model indicates that there is a relatively 34S-depleted H2S zone in the seawater at the same time. Combined with the understanding that the source of phosphorus in the phosphorite is closely related to the upwelling, it can be considered that the sulfur isotopic composition of phosphorite-associated sulfate of the Doushantuo Formation represents the mixed signal of surface seawater and upwelling.